Multi-Actor Innovative Framework in Effective Implementation of The Welfare Card and Affirmative Business Card Policy - Aminullah; Any Urwatul Wusko (Lembaga Bale Literasi, 2026)
This conceptual article examines the implementation effectiveness of two newly introduced Indonesian social assistance instruments, Welfare Card and Affirmative Business Card through a Multi-Actor Innovative Framework grounded in Sandfort and Moulton's Effective Implementation perspective. Within the 2026 national agenda to accelerate extreme poverty reduction through the National Socio-Economic Single Data (DTSEN) and targeted social assistance digitalization, persistent challenges of data integration and targeting accuracy remain critical concerns for policy implementation. This study adopts a qualitative policy-analysis design, synthesizing secondary data from government policy documents, official statements, and relevant academic literature. The analysis is organized around three interrelated strategic action fields proposed by Sandfort and Moulton: the policy field (national policymakers), the organizational field (implementing agencies and distribution channels), and the frontline field (social assistance facilitators and beneficiaries). Each field is examined in terms of power dynamics, institutional culture, inter-actor relationships, and operating rules, while the card-based assistance mechanism itself is analyzed as the core program technology linking policy intent to field-level practice. The discussion identifies potential coordination gaps, capacity mismatches, and strategic intervention points across actor levels that may shape implementation effectiveness. The article concludes that multi-actor coordination, supported by integrated data systems and contextualized frontline capacity building, is essential for the success of these new social protection instruments, and offers directions for future empirical research employing primary fieldwork to validate the proposed framework in specific local contexts.